Faiza Butt, Ruby Chishti, Masooma Syed - Vadehra Art Gallery (Vadehra Art Gallery, 2009)
Ataloue of an exhibition held at Vadehra Art Gallery, New Delhi 28 March - 20 April, 2009.
Keywords: Art & Design -- Art & Design; Exhibition Catalogues -- Exhibition Catalogues